Parainfluenza Virus in Hospitalized Adults: A 7-Year Retrospective Study. (28th May 2018) - Russell, Elliott; Yang, Amy; Tardrew, Sydney; Ison, Michael G
Abstract : Parainfluenza virus infection is associated with substantial morbidity and rare mortality in hospitalized adults. There is a clear need for novel preventive and therapeutic approaches to parainfluenza virus infection. Abstract: Background: Parainfluenza virus (PIV) is a cause of respiratory tract infection in children and the immunocompromised population, but its clinical manifestations, impact, and outcomes in hospitalized adults are not well studied. Methods: This retrospective study included adults (≥18 years old) admitted to Northwestern Memorial Hospital or Prentice Women's Hospital (both in Chicago, Illinois) between 1 August 2009 and 31 July 2016 with a positive molecular test result for PIV. Epidemiologic, clinical, and outcomes data were collected from the enterprise data warehouse and patient electronic health records after institutional review board approval. Descriptive statistics were used to summarize the data. Results: A total of 550 adults with a positive molecular test for PIV were identified. Differences in seasonality, clinical presentation, and prevalence between the different PIV serotypes (PIV-1, PIV-2, and PIV-3) were identified. The most common signs/symptoms were cough (88%), productive sputum (55%), fever (63%), and dyspnea (49%). Of the patients administered antibiotics, 349 (79.6%) had no confirmed bacterial infection throughout their hospitalization. The average length of hospitalization was 7.7 days. Presence of bacterial coinfection ( P = .01), fungal coinfection ( P < .01), decreased body mass index ( P = .03), and increased respiratory rate ( P < .01) were associated with significant differences in mortality rates. Conclusions: PIV infection is associated with substantial morbidity in hospitalized adults. Such data will be useful in understanding the impact on epidemiology and outcomes if a PIV-specific vaccine becomes available. Furthermore, this highlights the need for novel preventive and therapeutic approaches to PIV infection.